Sistem Informasi Penyewaan Kamar Menggunakan Metode Waterfall Dengan Konsep Pemrograman Berbasis Objek (Studi Kasus : Hotel Bonita Cisarua Bogor) - Fajar Agustini (Universitas Bina Sarana Informatika, 2017)
In current era of globalization, the information technology moving rapidly in various fields. As for developing the information was an information will be used again for making a decisions. Existing system in Hotel Bonita at the moment still manually, starting from data collection room to store other data associated with the process of ordering and rental of up to making its report. It is quite possible the occurrence of error in recording, made less accurate reports and delays in the search data that is needed. Base description upon, therefore done by service step-up at makings ordering area futsal's field. Field makings system futsal in here previous manual which will be developed as information system (computerized) in form one application . Desktop Application this was made by use of script PHP and Mysql database.Kata Kunci— Sistem Pakar, Penyakit Gigi, Dempster-Shafer.